Polyubiquitin chain editing by UCH37 promotes degradation of a subset of proteasome substrates - Dillon, Andrew Liam, author; Yao, Tingting, advisor; Cohen, Robert, committee member; Schauer, Grant, committee member; Ross, Eric, committee member; Prenni, Jessica, committee member (Colorado State University. Libraries, 2025)
Branched polyubiquitin can serve as a priority signal for proteasomal degradation by enhancing proteasomal degradation of modified substrates relative to substrates modified with homotypic K48-linked polyubiquitin chains. UCH37, a proteasome-associated deubiquitinating enzyme (DUB), has been shown to target the K48 linkage in branched polyubiquitin chains of diverse architectures. Additionally, this debranching activity has been shown to promote proteasomal degradation of branched chain-modified substrates in vivo and in vitro. However, it is unclear whether all branched chain-modified substrates require debranching by UCH37 to promote efficient proteasomal degradation. Additionally, how UCH37 debranching activity is coordinated with substrate processing on the proteasome remain unclear. Here, we set out to better understand the substrate specificity and functional consequences of UCH37 activity on the proteasome. Our work highlights that only a subset of branched chain-modified substrates is affected by UCH37, and proteotoxic stress enhances that dependence. In cells, loss of UCH37 activity leads to an enrichment of polyubiquitin and proteostasis factors on the proteasome and in the detergent-insoluble fraction of lysate as well as impaired degradation of the chromatin-bound branched chain-modified proteins BRD4 and SUV39H1, suggesting a preference for UCH37 in regulating degradation of chromatin-bound or otherwise aggregation-prone, tough-to-degrade protein substrates. These observations lead to a model that polyubiquitin processing by UCH37 is important to facilitate release of substrates stalled on the proteasome to promote proteasome recycling. Proteasome recycling by UCH37 is likely a critical mechanism to prevent accumulation of damaged or misfolded proteins and maintain overall cell health and functioning, especially under proteotoxic stress.
Keywords: polyubiquitin; RPN13; UCH37; proteasome; branched; ubiquitin